Conservative approach for treatment of maxillary lateral incisor agenesis with the deciduous tooth retained: 18-month follow-up - Lameira, C. E.C.M. [UNESP]; Mestrener, Sandra Rahal [UNESP]; Pini, N. I.P. [UNESP]; Salomão, F. M. [UNESP]; Pesqueira, Aldiéris Alves [UNESP]; Fagundes, Ticiane Cestari [UNESP] (Operative Dentistry, 2018)
This case describes a female patient with agenesis of the maxillary right lateral incisor, with her permanent canine in its position and the deciduous canine retained. Additionally, she presented with a maxillary left peg lateral incisor. To solve her functional and esthetic complaints, a multidisciplinary approach involving perio-restorative procedures was proposed. Periodontal surgeries were performed to align the gingival contour, and the restorative approach utilized ceramic veneers. At the 18-month clinical and radiographic followup, the treatment outcome was stable, with maintenance of the clinical results achieved and without any sign of deciduous tooth re-sorption.